Risk Factors for Post-operative Ileus: A Retrospective Study in Tertiary Referral Hospital in Indonesia - Sueta, Made Agus Dwianthara; Golden, Nyoman; Prawira, Mira Dewi (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Postoperative ileus is a complication that may result in the longer duration of stay and decreases the quality of life of patients. Previous studies have found some factors related to postoperative ileus. This study aimed to determine the risk factor of postoperative ileus in laparotomic resection and anastomosis surgery. Methods: Patients who underwent laparotomic resection and anastomosis surgery during January 2019 – July 2020 were included. Postoperative ileus was diagnosed in fourth day after surgery. The variables included in this study are age, gender, BMI, pathology site, duration of surgery, type of anastomosis, length of resection. Result: Fifty laparotomic resection and anastomosis surgery patients were included in this study, 50% of subjects is patients with postoperative ileus. Patient aged 65 years old or older had a higher incidence postoperative ileus (68% vs 28%; RR 2.3 95% CI: 1.23-4.33; p value: 0.010). Study also found duration of surgery 180 minutes or longer also had higher incidence postoperative ileus (79% vs 36%; RR: 2.49 95% CI: 1.20-5.15; p value: 0.010). Conclusion: This study concludes that age 65 years old or older and duration of surgery 180 minutes or longer are significant risk factor to postoperative ileus in laparotomic resection and anastomosis surgery patients.